Learning Strategy of Akidah Akhlak Subject During Covid-19 Pandemic in Madrasah Ibtidaiyah - Andi Anirah; Naima Naima; Khaeruddin Yusuf; Erni Palinge (Institut Agama Islam Negeri Imam Bonjol Padang, 2023)
The Covid-19 pandemic causes many problems which forced teachers to innovate and determine the learning strategies used. The strategy was chosen based on the nature or subject material character. Akidah Akhlak was a compulsory subject in Madrasah Ibtidaiyah. This study aimed to analyze the teacher's strategy in the learning of Akidah Akhlak Subject at MIN Palu during the pandemic. The design of this research was descriptive qualitative research with a phenomenological approach. The data were obtained from interviews, observations and documentation. The study results showed that the Akidah Akhlak learning strategy was implemented in two learning models, namely Online and Offline (Home Visit). The first was online learning by using smartphones and laptops with the WhatsApp application, video calls, google classroom, and Ruang Guru Application. The second was student's home visits by gathering some students who lived nearby to each other's house to study together and assignments were given every week based on a schedule. The home visit is prioritized for students who were categorized as slow learners and students without internet connection. In online learning and home visits, creativity and optimizing the roles of teachers and parents are very necessary for the effective and efficient learning. These findings can be used as input in determining future learning strategies